Pengaruh Budaya Organisasi, Kompensasi terhadap Kepuasan Kerja dan Kinerja Pegawai Bank di Surabaya - Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2016)
Along with the bank's growth in Indonesia, one of the problems faced by the world is handling domestic banks that are now on the quality of human resources. Because human resources are the backbone of the operating activities of wheels and the survival of a company. In this case oriented to customer satisfaction and service organization of Bank Syariah Mandiri Surabaya CFBC Division there are also aspects of cultural values and compensation to improve morale and satisfy the desires of employees. The approach in this study is a quantitative approach, which used the data type is the kind of quantitative data. Data collection techniques performed by researchers are using questionnaires. The population in this study are employees on Shariah Bank Mandiri as many as 30 people. Teknik data analysts use Structural Equation Model-Partial Lest Square (SEM-PLS). The results showed that 1) organizational culture influence on job satisfaction. (2) Organizational culture influence on performance (3) Job satisfaction terhaap affect performance (4) Compensation effect on job satisfaction (5) Compensation effect on performance.